Mental Health Promotion: Stop Self-Diagnosing Through Social Media - Gobel, Sry Ade Muhtya; Elnovani Lusiana; Susanne Dida (Universitas Airlangga, 2023)
Background: Mental health is increasingly being recognized as a severe problem. While there has been an increasing awareness of mental health and psychological well-being for economic and social development over the past two decades, there has not been a corresponding increase in mental health investment. Social media platforms allow healthcare practitioners to take full advantage of the potential of social media. However, this good thing is followed by a bad thing, where more and more information is accessible; people use that information to benchmark that they also have a